ANALISIS PEMBIAYAAN PROPERTI MENGGUNAKAN AKAD MUSYARAKAH MUTANAQISAH PADA PERUMAHAN GRIYA HARTACU PATTALLASSANG KABUPATEN GOWA - Jumarni, Jumarni; Fathurrahman, Fathurrahman; Katman, Muhammad Nasri (Investama : Jurnal Ekonomi dan Bisnis, 2023)
The Griya Hartacu Pattallassang Housing Complex, Gowa Regency has two financing agreements used and is one of the subsidized housing under the care of PT.  Three Great Revas.  This housing uses financing agreements, including the Murabahah KPR contract, and the Musyarakah Mutanaqisah contract.  The researcher himself focuses on the musyarakah mutanaqisah financing contract.  This study aims to find out how the Musyarakah Mutanaqisah contract is implemented, and how the Musyarakah Mutanaqisah contract is compatible with the Fatwa of the National Sharia Council No.  73/DSN-MUI/XI/2008.  The formulation of the problem is: (1), How is the Musyarakah Mutanaqisah contract implemented in the financing process for the Griya Hartacu housing in Pattallassang?  (2), Is the transaction process for musyarakahmutanaqishah financing contracts in accordance with the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) No.  73/DSN-MUI/XI/2008?.  This research is a field research using qualitative research.  This research approach uses descriptive qualitative.  The subject of this research is the people who live in Griya Hartacu Pattallassang housing.  Data collection techniques were carried out by observation, interviews and documentation.  The data validation technique uses theory and source triangulation techniques by collecting data and information from a variety of different sources.  The results of this study indicate that financing for the Griya Hartacu Pattallassang housing uses two financing agreements, namely a murabahah mortgage contract, and a musyarakahmutanaqisah contract.  These two contracts are also very influential in the transaction process of the people who are the actors in the two contracts.  The musyarakahmutanaqisah contract is reviewed with the Fatwa of the National Sharia Council No.  73/DSN-MUI/XI/2008, researchers have analyzed and reviewed and then researchers found that the financing of the musyarakahmutanaqisah contract is in accordance with the DSN-MUI fatwa, but the contract has not been fully used, only some buyers use the contract in the home buying process.